Partisipasi Masyarakat Dalam Upaya Pencegahan Stunting di Desa Huangobotu Kabupaten Bone Bolango - Akuba, Abdul Mukhlis; Agussalim, Alfiyah; Pakaya, Rahmatia (Innovative: Journal Of Social Science Research, 2024)
Stunting is a public issue that requires immediate handling because it has a large enough impact to become a major threat to the quality of human resources and a threat to the nation's competitiveness. To prevent and deal with stunting, apart from government efforts, active community participation is also needed. Therefore, this research is aimed at finding out the participation of the Huangobotu Village community in preventing stunting. This research focuses on 1) Environmental health; 2) Mother's knowledge about health and nutrition; 3) Parents' busyness; and 4) Poverty. From the research results, it was found that community participation was still moderate, especially in the focus of mothers' knowledge about fulfilling nutrition and in families whose economic conditions were still low.